PSYCHOLOGICAL APPROACH TO DETERMINING CHILDREN’S TALENT - Toshpulatov Ibrohim Ikromjonovich; Xakimova Dilshoda Kamoljon qizi (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2024)
As we all know, our future is in the hands of the young generation. Today, not only parents, but everyone in our society is equally responsible for improving children’s talents and abilities. A country whose children are knowledgeable, talented, and have high potential always achieves high goals. In today’s article, we will consider how effective the psychological approach is in improving children’s talent and their cognitive potential.